2004
DOI: 10.1104/pp.104.045823
|View full text |Cite
|
Sign up to set email alerts
|

Promoter Analysis of the Barley Pht1;1 Phosphate Transporter Gene Identifies Regions Controlling Root Expression and Responsiveness to Phosphate Deprivation

Abstract: Previous studies have shown that the promoter from the barley (Hordeum vulgare) phosphate transporter gene, HvPht1;1, activates high levels of expression in rice (Oryza sativa) roots and that the expression level was induced by up to 4-fold in response to phosphorus (P) deprivation. To identify promoter regions controlling gene regulation specificities, successive promoter truncations were made and attached to reporter genes. Promoters of between 856 and 1,400 nucleotides activated gene expression in a number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(90 citation statements)
references
References 27 publications
4
85
0
Order By: Relevance
“…Transcriptional activation of these genes has been attributed to the interaction of the MYB transcription factor PHR1 with the P1BS element in the promoter of these genes (7). Recently, additional evidence based on experimentation by using HvPht1;1 has supported the possibility that the P1BS element has a transcriptional activation function (37). Our determination that AtSIZ1 participates in the sumoylation of PHR1 (Fig.…”
Section: Atsiz1 Acts Also As a Positive Regulator Of Some Pi Starvationmentioning
confidence: 79%
“…Transcriptional activation of these genes has been attributed to the interaction of the MYB transcription factor PHR1 with the P1BS element in the promoter of these genes (7). Recently, additional evidence based on experimentation by using HvPht1;1 has supported the possibility that the P1BS element has a transcriptional activation function (37). Our determination that AtSIZ1 participates in the sumoylation of PHR1 (Fig.…”
Section: Atsiz1 Acts Also As a Positive Regulator Of Some Pi Starvationmentioning
confidence: 79%
“…6A). The P1BS cis-acting element (PHR1-binding site [GNATATNC]; Rubio et al, 2001;Schü nmann et al, 2004) was found in the promoter region of PtPT1, PtPT4, PtPT7, PtPT10, PtPT11, and PtPT12. The P1BS element and the CTTC motif (CTTCTTGTTCTA; Karandashov et al, 2004) were found in close proximity to each other within the 200 bp upstream of the ATG start codon of PtPT10 and PtPT12 and a set of other AM-specific Pi transporter genes (Fig.…”
Section: Coregulation and Interspecific Conversation In Pht1 Gene Expmentioning
confidence: 99%
“…They are tip-growing extensions originating from root epidermal cells, so-called trichoblasts, which play an important role in water and nutrient uptake (reviewed by Datta et al 2011). Root hairs are the major site of inorganic P uptake (Pi, phosphate) (Gahoonia and Nielsen 1998) containing the high affinity phosphate transporters responsible for P i uptake (Mudge et al 2002;Schunmann et al 2004), and transporters for ammonium and nitrate (Lauter et al 1996). Tip growth in plant cells is an actin-based process that requires targeted exocytosis and compensatory endocytosis to occur at the growth cone and involves polarised membrane trafficking and the presence of endosomal compartments at the tip of root hairs (Ovecka et al 2005;Voigt et al 2005).…”
Section: Do Root Hairs Provide a Path For Large Molecule Into Roots?mentioning
confidence: 99%